Role of ferroptosis in hypoxic preconditioning to reduce propofol neurotoxicity - Chen, Jing; Xiao, Fei; Chen, Lifei; Zhou, Zhan; Wei, Yi; Zhong, Yu; Li, Li; Xie, Yubo (Frontiers in Pharmacology, 2023)
Background: An increasing number of studies have reported that neurotoxicity of propofol may cause long-term learning and cognitive dysfunction. Hypoxic preconditioning has been shown to have neuroprotective effects, reducing the neurotoxicity of propofol. Ferroptosis is a new form of death that is different from apoptosis, necrosis, autophagy and pyroptosis. However, it is unclear whether hypoxic preconditioning reduces propofol neurotoxicity associated with ferroptosis. Thus, we aimed to evaluate the effect of propofol on primary hippocampal neurons in vitro to investigate the neuroprotective mechanism of hypoxic preconditioning and the role of ferroptosis in the reduction of propofol neurotoxicity by hypoxic preconditioning. Methods: Primary hippocampal neurons were cultured for 8 days in vitro and pretreated with or without propofol, hypoxic preconditioning, agonists or inhibitors of ferroptosis. Cell counting kit-8, Calcein AM, Reactive oxygen species (ROS), Superoxide dismutase (SOD), Ferrous iron (Fe2+), Malondialdehyde (MDA) and Mitochondrial membrane potential assay kit with JC-1 (JC-1) assays were used to measure cell viability, Reactive oxygen species level, Superoxide dismutase content, Fe2+ level, MDA content, and mitochondrial membrane potential. Cell apoptosis was evaluated using flow cytometry analyses, and ferroptosis-related proteins were determined by Western blot analysis. Results: Propofol had neurotoxic effects that led to decreased hippocampal neuronal viability, reduced mitochondrial membrane potential, decreased SOD content, increased ROS level, increased Fe2+ level, increased MDA content, increased neuronal apoptosis, altered expression of ferroptosis-related proteins and activation of ferroptosis. However, hypoxic preconditioning reversed these effects, inhibited ferroptosis caused by propofol and reduced the neurotoxicity of propofol. Conclusion: The neurotoxicity of propofol in developing rats may be related to ferroptosis. Propofol may induce neurotoxicity by activating ferroptosis, while hypoxic preconditioning may reduce the neurotoxicity of propofol by inhibiting ferroptosis.